An integrated micro electro mechanical system–based silicon wet etching process and nano carbon materials used for improving micro direct methanol fuel cells performance. (June 2021) - Yang, C.-R.; Fu, P.-C.; Cheng, C.; Huang, M.-J.
Abstract: This study integrates "TMAH wet etching" "photo-assisted electrochemical etching', "PtRu binary metal chemical plating", and "methanol modification" techniques to develop a micro direct methanol fuel cell. The battery electrode plate is made into microchannel + porous silicon (PS) and microchannel + through-silicon via (TSV) plate electrodes using a silicon wafer as the substrate. When the anode and cathode use a PS electrode and TSV electrode, respectively, the maximum open-circuit voltage is 0.4 V, which is 1.5 times the cell using the PS electrode and 6.7 times the cell using the TSV electrode. The PtRu binary metal is uniformly coated on the surface of a graphene and carbon nanotube to form a compound catalyst layer (PtRu/G-CNT), where the Pt and Ru contents are 34.1 wt% and 2.6 wt%, respectively. In the half-cell test, the oxidation current peak of PtRu/G-CNT is 5 mA/cm 2, which is 2.02 times and 2.4 times that of Pt/G-CNT and PtRu/G, respectively. When the fuel is mixed with 0.1% surfactant of sodium dihexyl sulfosuccinate, the maximum power density is 0.336 MW/cm 2, and the maximum open-circuit voltage is 0.48 V, which are 1.4 times and 1.2 times the case without a surfactant, respectively. Graphical abstract: Image 1 Highlights: The whole silicon cell applies mature and low-cost production technology. Three compound catalyst layers of Pt-Ru/G-CNT, Pt/G-CNT, and Pt-Ru/G are used and investigated. Discussion and comparison for diffusion layer structures using porous silicon and through-silicon via. A surfactant enhances the power density and open-circuit voltage of micro direct methanol fuel cell.